2000
DOI: 10.1002/(sici)1097-4636(20000305)49:3<415::aid-jbm15>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and release of insulin-like growth factor-I on porous tricalcium phosphate implant

Abstract: Abstract:In order to develop bone substitutes, the design of biomaterials like calcium phosphate ceramic loaded with bone growth factor are of great interest. However, it is necessary to control the amount of growth factor adsorbed onto ceramics and the kinetics of its release. Radiolabeling of insulin-like growth factor-I (IGF-I) with 125-iodine ([ 125 I]-IGF-I) and its adsorption onto porous tricalcium phosphate (TCP) cylinders enabled us to establish the time-adsorption and time-release curves using various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…For example, Laffargue et al loaded IGF-1 onto porous tricalcium phosphate cylinders via adsorption in vitro and reported significant IGF-1 release up to day 4 followed by much slower release up to day 20. 45 At the end of this experiment up to 60% of the adsorbed IGF-1 remained on these matrices, indicating a strong binding interaction. 45 Protein adsorption on to collagen membranes is mainly due to hydrogen bonding and ionic bonding between the collagen and the diffusing protein, and adsorption is proportional to both the number of sites available for binding and the protein concentration.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…For example, Laffargue et al loaded IGF-1 onto porous tricalcium phosphate cylinders via adsorption in vitro and reported significant IGF-1 release up to day 4 followed by much slower release up to day 20. 45 At the end of this experiment up to 60% of the adsorbed IGF-1 remained on these matrices, indicating a strong binding interaction. 45 Protein adsorption on to collagen membranes is mainly due to hydrogen bonding and ionic bonding between the collagen and the diffusing protein, and adsorption is proportional to both the number of sites available for binding and the protein concentration.…”
mentioning
confidence: 66%
“…45 At the end of this experiment up to 60% of the adsorbed IGF-1 remained on these matrices, indicating a strong binding interaction. 45 Protein adsorption on to collagen membranes is mainly due to hydrogen bonding and ionic bonding between the collagen and the diffusing protein, and adsorption is proportional to both the number of sites available for binding and the protein concentration. 46 Previously, the uptake of IGF-1 into normal human cartilage was studied, and binding experiments indicated that the growth factor binds to proteoglycans.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…5,6 However, these factors could not induce osteogenesis. In this regard, bone morphogenetic proteins (BMPs), consisting of a multiplemembered family, BMP-2 to BMP-13, can induce…”
Section: Introductionmentioning
confidence: 99%